Hardware/Software interface for enhanced remote control of Android set-top-box - Santos, Ricardo Alexandre Caseiro dos (2016)
This dissertation describes the research and development of a communication system to support remote control devices (RCD) for Android-based set-to-box (STB). The target RCD is a low-complexity device using 3D motion tracking to provide new interactive functionalities to di erent types of multimedia content and applications. The system architecture comprises an RCD with Magnetic, Angular Rate, Gravity (MARG) unit for 3D motion tracking, transmitting data to an Android STB. The communication between the RCD and the STB was implemented using the Radio Frequency for Consumer Electronics (RF4CE) protocol, which required the development of an external module for the STB. An Application Programming Interface (API) was developed to enable seamless computation of the remote control data and allowing six input pro- les on the Android: Absolute air mouse, Relative air mouse, multitouch, accelerometer, gyroscope and magnetometer. To allow the sensors from the MARG unit in the remote control device to be natively recognized on the Android OS, an Android sensors library was also developed, this reads the sensors data from the API. The demonstration of the system functionalities was done through an Android application speci cally developed to simulate and test a potential usage environment. A study to nd out whether the most complex functions should run on the RCD or on the Android STB was also carried out. The optimal solution still remains an open issue since it depends on the speci c application and portability requirements taking into account energy consumption. The analysis of energy consumption on the RCD shows that transmitting the raw data from the sensors to be processed in the API, results in a lower energy consumption, and consequently higher portability with good accuracy. Since the STB has no limitations on energy consumption and superior computational power, the API was designed to be able to perform all the processing of sensors data, thus allowing the implementation of complex fusion algorithms with higher precision.